STUDI PENGARUH WAKTU REAKSI TERHADAP SINTESIS SENYAWA ORGANONITROGEN BERBASIS α-PINENA MELALUI REAKSI RITTER - Rahman, Mohammad Farid; Ulfa, Siti Mariyah; Fatma, Aliya (Jurusan Kimia, FMIPA Universitas Brawijaya, 2013)
The aim of this research is to synthesize organonitrogen compound using α-pinene as starting material which reacted with acetonitrile and acid catalysts through Ritter reaction. The reactions were optimized by modifying a reaction time varied from 6, 10, and 15 hours. α-Pinene used in this reaction was isolated from turpentin oil by fractional distillation in 88.46%. There were three major products obtained from reaction of α-pinene, acetonitrile and H2SO4 97%, that is, N-(2,6,6-trimethylbicyclo[3.1.1]heptan-2-yl)acetamide as product 1, N-(2-(4-methylcyclohex-3-enyl)propan-2-yl) acetamide as product 2, and N-(1,7,7-trimethylbicyclo[2.2.1] heptan-2-yl)acetamide as product 3. The percentage of product 2 and product 3 were increased by the increasing of reaction time, while product 1 was decreased. This result is considered by different stability of product structure. Product 2 and 3 should be the most stable structure than product 2. The other acetamide derivatives were also produced but in low percentage. Key words: α-pinena, Ritter reaction, acetamide compound, organonitrogen compound, reaction time